Microfinance and development in emerging economies : an alternative financial model for advancing the SDGs - Malhotra, Nishi (Emerald Publishing Limited, 2023)
Globally, 1.7 billion people live in poverty and are unable to access financial services. They do not have physical collateral and creditors are reluctant to invest in them. Yet in India, microfinance is being used to reduce poverty, empower women, and boost development. In Microfinance and Development in Emerging Economies, Nishi Malhotra argues that the financial services provided to low-income groups or individuals through microfinance and group lending outside the traditional financial system are the best way to combat these problems and address the economic exclusion that blights so many. Using India as a case study, Malhotra examines the Indian government's use of various social welfare programmes to increase both financial literacy and social equality and ultimately achieve sustainable development. Suitable for bankers, teachers, policymakers, and students, this book clearly identifies the practical and theoretical implications of this alternative microfinance model.
Keywords: Microfinance -- India.; Sustainable development -- India.; Microfinance -- Case studies.; Business & Economics -- Finance -- General.; Finance.; elektronické knihy; electronic books